The Greek world - Powell, Anton (Routledge, 1995)
This ground-breaking new collection contains twenty-seven articles by specialists in ancient Greek history. Periods studied range from the Mycenaean to the late Hellenistic; the Greek cultures in question are not only those of mainland Greece, but also include Asia Minor, Egypt and Italy. Many of the essays in The Greek World are concerned with social history, especially the history of those who were at or beyond the margins of society such as women, the poor and slaves. In keeping with modern interests, several of the contributors look at those who were geographically at the edges of the Greek world. However, there is no disengagement here from the more traditional interests of classical scholarship. The Greek World shows how research into areas once considered peripheral can shed vital light on topics traditionally seen as central. Herodotus' work on Egypt is shown to reflect on his credibility as a source for Greek history. Plato's reforms are illuminated through a consideration of his impatient and revolutionary attitude to women. The most potent symbol of old-fashioned 'central' Greek history, the Parthenon, is shown to be understood more fully given a knowledge of the cosmetic techniques of (and gossip about) Athenian women. Social and political history interact in this volume, to the enlightenment of both.